LINC02163 promotes colorectal cancer progression via miR-511-3p/AKT3 axis - Junwen Ma; Lihai Zhang; Anquan Shang; Hu Song; Jiege Huo; Mingjian Zhang; Liuqin Jiang (Artificial Cells, Nanomedicine, and Biotechnology)
Long non-coding RNAs and microRNAs are functional regulators in tumour progression. Herein, we revealed the level LINC02163 was up-regulated in CRC tissues and cell lines, and the expression of LINC02163 negatively correlated with prognosis of CRC patients. Functional experiments demonstrated knockdown of LINC02163 significantly attenuated CRC cells proliferation and metastasis. Mechanism analysis showed miR-511-3p could bind LINC02163 and AKT3, and the expressional level of miR-511-3p negatively correlated with the abundance of LINC02163 and AKT3. Inhibition of LINC02163 suppressed cell proliferation, while transfection of miR-511-3p inhibitor or AKT3 in LINC02163-depletion cells restored cell growth and abolished the cell cycle arrest in G0/G1 phase. Therefore, it was indicated that LINC02163 exerted pro-tumour effect through miR-511-3p/AKT3 axis and was prognostic marker for colorectal cancer.